İnşaat sektörüne küresel bakış - Eşkinat, Rana; Tepecik, Filiz (Afyon Kocatepe Üniversitesi, 2012)
Teknolojik gelişmelere bağlı olarak zaman ve mekân farkının yok olduğu bir dünyada yaşıyoruz. Giderek küçülen ve kontrol altına alınan bu dünyanın insan eli ile yeniden inşa edildiğini düşünüyoruz. Bu çalışmada teknolojik gelişmeleri, küreselleşmeyi ve inşaat sektörünü birbirleri ile ilişkilendirerek ele alıyoruz. İnşaat sektörünün yerel, ulusal, bölgesel, küresel ilişkilerden oluşan karmaşık yapısını anlamaya ve bu yapı içinde Türk inşaat sektörünün yerini bulmaya çalışıyoruz. Böylece içinde yaşadığımız dünyayı kavramaya yardımcı sonuçlara ulaşmayı umuyoruz.

Technological improvements provide us an earth without time and space restrictions. We think that this smaller and much more controllable world have been created by the construction activities of people. In this paper we focus on technological improvements, globalization and construction sector in relation with each other. We try to understand the complex nature of the construction sector. There are local, national, regional and global links between different elements and actors of the sector. We try to understand the place of Turkish constructors in this complexity of the sector and try to reach helpful results in order to understand complexity of our world order.
Keywords: Globalization; Turkish Construction Sector; Integration to Capitalism